PENGIRIMAN KARGO DANGEROUS GOODS DI WAREHOUSE PT JASA ANGKASA SEMESTA HALIM PERDANAKUSUMA - Rini Setiawati; Ralind Rickson Dollys P.; Noor Syamsu Hidayat (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
PT Jasa Angkasa Semesta Services Halim Perdana Kusuma is a company engaged in the ground and cargo handling. The purpose of this study is to determine the effect of handling the acceptance process to the smooth delivery of cargo dangerous goods at the company. The research method used is quantitative method with simple linear regression analysis, correlation coefficient analysis, coefficient determinant and hypothesis test. Based on the result of the analysis, regression equation Y = 5,521 + 0,809X means that every increase / decrease of variable X (Acceptance Process Handling) will result in increase / decrease of variable Y (Cargo Delivery Frequency Dangerous Goods) equal to 0.809 units at constant 5,521. Correlation coefficient (r) of 0.744, there is a strong and positive influence between X and Y. The determinant coefficient (KP) of 55.3% that the contribution of variable X affect the change and fall of Y variable 55.3% and the remaining 44.7 % influenced by other factors. Hypothesis test results show t-count t-table (6,865≥1,686), then Ho is rejected and H1 accepted, it means there is a strong and positive influence between the acceptance process handling towards the smooth delivery of dangerous goods cargo at Warehouse PT Jasa Angkasa Semesta Halim Perdana Kusuma 2015.